HASIL DESTILASI KERING DAN NILAI KALOR KAYU NANGKA (Artocarpus heterophyllus Lamk) - srii komarayat; Djeni Hendra (Jurnal Penelitian Hasil Hutan, 1992)
Rapid destructive of Jackfruit wood was carried out by using a retort equipped with electrical heating syslem. This retort was also connected to a condenser and two flask to catch and  collect  the distillate or condensed gas.  The retort capacity was about  4 kg of wood.  Treatment conditions given in these experiment  were maximum heating temperature of500ᵒ C and 5 hours  distillation time.The results showed that charcoal yield of Jackfruit  wood varied from  25.00  to 39.81%, tar from  6.23 to 9.42%  and pyroligneous liquor from  67.64 to 102.05%  The calonfic  value of wood varied from  4392.00  to 4620. 65  kcal/g and charcoal from 6691.81 to 7108.37.kcal/g.Based on  these calorific values, wood and charcoal of Jackfruit wood are excellent material for fuel.